Holocene Paleohydrology of the St. Elias Mountains, British Columbia and Yukon - Johnson, Peter (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTThe evolution of the Holocene paraglacial environment of the St. Elias Mountains has been dominated by hydrological variations which modify the direct glacial depositional environment and trigger instabilities in valley side glacial and talus deposits. Data from the Kaskawulsh Glacier demonstrate how discharge and sediment transport regimes vary through the season, as sediment is flushed out of the system, and a marginal to subglacial drainage change of the Grizzly Creek Glacier illustrates the effects of extraordinary events in transporting large volumes of sediment. A multiple glacier fluctuation model applied to the region produces rapid temporal changes in discharge and sediment regimes throughout the Holocene. The effect of these variations is enhanced by the occurrence of surges of many of the glaciers of the St. Elias Mountains and by sequences of glacier dammed lake formation and drainage in the region.